ISLAMIC SOCIAL FINANCING FOR SMART WAST MANAGEMENT: A STUDY ON UTILIZING WAQF FOR AI-DRIVEN WASTE SORTING AND RECYCLING TECHNOLOGIES - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Shafa’at Ahmad Aliyu; Muhammadu Sani Abubakar; Bala Babangida (INTEGRATIVE : Journal of Economics, Management, Business and Accounting, 2026)
This study examines the potential funding of AI-powered waste management systems that support sustainable urban expansion using Islamic social finance, namely waqf (Islamic endowments). The more people living in an urban area, the more difficult it is to sort, collect, and recycle waste, which calls for substantial financial resources and innovative solutions. With the use of waqf, this study investigates how Islamic social finance might provide a morally sound and long-lasting funding method for AI-powered automated waste sorting and recycling systems. The study looks at the alignment between Islamic environmental stewardship principles and modern waste management goals. It focuses on how waqf can be set up to support AI technologies that improve waste sorting accuracy, reduce dependency on landfills, and increase resource efficiency. The study highlights how waqf can encourage waste management innovation, which will ultimately support sustainable urban expansion and the goals of the circular economy. By examining case studies of existing waqf-funded environmental projects, a framework for implementing waqf-financed, AI-integrated waste management systems in towns with a majority of Muslims is proposed. The results show that communities can solve waste management issues in a sustainable manner and create an environmental care model that is in line with Islamic norms by setting up specialized "green waqf" funds.